Two new self-adaptive algorithms for solving split common fixed point problems with multiple output sets - Sun, Wenlong; Jin, Yuanfeng; Peng, Zufeng; Liu, Qi (Optimization, 2024)
In this paper, we study split common fixed point problems with multiple output sets in Hilbert spaces. For solving this problem, we improve Reich and Tuyen's algorithms [10] and propose two new self-adaptive algorithms which do not need any priori information on the norms of the transfer operators. Then, we establish weak convergence theorems for them. It can be seen from our numerical experiments that the proposed methods depict a very significant improvement in terms of the number of iterations and execution time.